Research on main influencing factors and complete support technology for dynamic pressure and large deformation roadway - Hai Rong; Kaipeng Guo; Dequan Sun; Mingkun Luo; Wei Dong; Bingjie Huo (Scientific Reports, 2023)
Abstract To determine the main factors influencing dynamic pressure and large deformation roadways, a targeted set of support technologies was designed. The 2603 air inlet roadway of the Zhangcun coal mine in Lu'an, Shanxi Province, was taken as an example. The influence of the Wenwangshan South normal fault and in situ stress field on the dynamic pressure roadway was analyzed theoretically, and the main factors influencing this dynamic pressure and large deformation roadway under natural geological conditions were determined. The effect of the existing roadway support scheme was evaluated by field test methods such as nondestructive bolt testing. The influence of mining two working faces on the dynamic pressure and large deformation roadway was studied by the FLAC3D numerical simulation method. On this basis, a new grouting material was developed, a complete set of technical schemes of full-section integrated cooperative support of dynamic pressure and large deformation roadways was proposed, and the field application effect was verified. The results showed that under natural geological conditions, the 2603 air inlet roadway was located within the influence range of the Wenwangshan South normal fault, which was significantly affected and controlled by the fault. The included angle between the roadway extension direction and the maximum principal stress was 74°, which was not conducive to the stability of the roadway. The range of the roadway loose zone was large. Under the existing support conditions, the surrounding rock could not form a relatively stable structure, which was one of the main reasons for the large deformation of the surrounding rock in the dynamic pressure roadway. The 2603 air inlet roadway was affected by the mining of both the adjacent working face and the 2603 working face. The stresses were superimposed, and the roadway was greatly deformed and damaged. A new grouting material was developed. A crosslinking agent prepared by toluene diisocyanate and polyether polyol was added to the existing polyurethane material to form a new grouting material, and a complete supporting technical scheme was proposed. The field application results showed that the displacement and floor heave of both sides of the roadway were reduced by approximately 87%, the deformation and failure of the coal and rock mass of the roadway were effectively controlled, and the deformation of the dynamic pressure roadway was greatly reduced.